The Writing Skill Benefits of Increased Students' Reading Comprehension: A Case Study at Universitas Kristen Indonesia - Simatupang, Astri Julianti (JET (Journal of English Teaching), 2017)
This research was conducted to investigate the correlation between reading comprehension and writing skill at the Faculty of Education and Teacher Training, Universitas Kristen Indonesia. The sample data were taken based on the scores of Reading I, Reading II, Reading III, Reading IV, and Reading V and Writing I, Writing II, Writing III, Writing IV and Writing V. The participants were 30 raguler students in the eighth semester of 2012 batch of English Teaching Study Program students, Faculty of Teacher Training and Education, Universitas Kristen Indonesia students. The collected data were analyzed by using SPSS version 24. The result showed that there was significance and strong correlation between reading comprehension and writing skill. some recommendations are provided to meet the objective of learning English as a foreign language in Indonesia and to provide a potential access to the further research.